Social media and the possibility of depressive states in young adults - Świdziński, Rafał; Gryc, Anna; Golemo, Jagna; Nowińska, Aleksandra; Lipiec, Jakub (Journal of Education, Health and Sport, 2022)
Social media (SM) is now a popular place for content creation and a means of communication between young adults. Their increasing participation in our lives means that they replace us face to face contacts (FTF), which can affect our mental health. The above changes in communication habits may correlate with the occurrence of depressive states and a sense of social isolation. The aim of the study is to analyze the relationship between the use of MS and the occurrence of depressive states in young adults on the basis of selected literature. The topic of emotional support and a sense of social isolation will also be discussed. PubMed and Google Scholar databases were used to select the appropriate literature, and only research was used. The cited studies on the use of MS and depression showed that people who spent the most time on social media showed an increased risk of experiencing a depressed mood. Another study analyzed the likelihood of depression depending on the method of emotional support. The comparison of emotional support in FTF (face to face) communication with the support obtained through MS showed that the possibility of depressive symptoms was lower for FTF communication and higher for the second method, respectively. The use of social media among young adults contributes to an increased risk of depression, perceived social isolation and reduced emotional support. Moreover, it has been proven that addiction to MS positively correlates with the presence of depressive symptoms.